GPA AS A STRONGER DETERMINANT OF MEDICAL DOCTOR COMPUTER-BASED NATIONAL COMPETENCE TEST - Tih, Fen; Waty, Wenny; Rizamena, Melya Ikbar; Sanjaya, Ardo; Gunadi, Julia Windi (Universitas Gadjah Mada, 2025)
Background: The government implements a high-quality assurance system in the health sector to strengthen the national education system. One of the steps is the Indonesian Medical Doctor National Competency Examination (known as UKMPPD in Indonesia), which follows regulations on higher education and health workers. The entrance exam for medical students at the Faculty of Medicine, Maranatha Christian University, consists of a biology test and an academic potential test.Aims: The purpose of this study was to determine the relationship between the biology entrance exam, academic potential test, and grade point average with the final score of UKMPPD CBT at the Faculty of Medicine, Maranatha Christian University. Methods: The samples collected consisted of students from the Faculty of Medicine at Maranatha Christian University, from the 2010 to 2016 classes, who took the UKMPPD from 2016 to 2022. Data were analyzed using the Spearman test and examined for both bivariate and multivariate relationships.Results: This study showed that the biology entrance examination, medical undergraduate GPA, and medical professional GPA influenced the UKMPPD CBT final score of Maranatha Christian University Faculty of Medicine students. Nevertheless, there is no relationship between students’ TPA score and UKMPPD CBT.Conclusion: Medical undergraduate GPA had the strongest relationship with CBT scores, compared to medical professional GPA. This study also highlighted the importance of non-cognitive aspects of input selection tests besides the improvement of the quality of the clinical education evaluation process.